Safety and possible anti-inflammatory effect of paclitaxel associated with LDL-like nanoparticles (LDE) in patients with chronic coronary artery disease: a double-blind, placebo-controlled pilot study - Marinho, Lucas Lage; Rached, Fabiana Hanna; Morikawa, Aleksandra Tiemi; Tavoni, Thauany Martins; Cardoso, Ana Paula Toniello; Torres, Roberto Vitor Almeida; Assuncao, Antonildes Nascimento; Serrano, Carlos Vicente; Nomura, Cesar Higa; Maranhão, Raul Cavalcante (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Studies in cholesterol-fed rabbits showed that anti-proliferative chemotherapeutic agents such as paclitaxel associated with solid lipid nanoparticles (LDE) have marked anti-atherosclerotic effects. In addition, association with LDE nearly abolishes paclitaxel toxicity. We investigated whether treatment with LDE-paclitaxel changes plaque progression by coronary CT angiography and is safe in patients with chronic coronary artery disease.We conducted a prospective, randomized, double-blind, placebo-controlled pilot study in patients with multi-vessel chronic coronary artery disease. Patients were randomized to receive IV infusions of LDE-paclitaxel (paclitaxel dose: 175 mg/m 2 body surface) or LDE alone (placebo group), administered every 3 weeks for 18 weeks. All participants received guideline-directed medical therapy. Clinical and laboratory safety evaluations were made at baseline and every 3 weeks until the end of the study. Analysis of inflammatory biomarkers and coronary CTA was also performed at baseline and 4 weeks after treatment.Results: Forty patients aged 65.6 ± 8 years, 20 in LDE-paclitaxel and 20 in placebo group were enrolled. Among those, 58% had diabetes, 50% had myocardial infarction, and 91% were in use of statin and aspirin. Baseline demographics, risk factors, and laboratory results were not different between groups. In all patients, no clinical or laboratory toxicities were observed. From the baseline to the end of follow-up, there was a non-significant trend toward a decrease in IL-6 levels and hsCRP in the LDE-paclitaxel group (-16% and -28%, respectively), not observed in placebo. Regarding plaque progression analysis, variation in plaque parameter values was wide, and no difference between groups was observed.In patients with multivessel chronic coronary artery disease and optimized medical therapy, LDE-paclitaxel was safe and showed clues of potential benefits in reducing inflammatory biomarkers.